PENGUATAN PERAN KADER POSYANDU DALAM PENCEGAHAN KEK PADA IBU HAMIL MELALUI PELATIHAN DAN PENDAMPINGAN - Nitta Isdiany; Mamat Rahmat; Mona Fitria (Poltekkes Kemenkes Bandung, 2026)
Chronic Energy Deficiency (CED) among pregnant women remains a public health problem in Indonesia because it increases the risk of low birth weight, preterm birth, and stunting. Prevention efforts require the active involvement of Posyandu cadres as frontline community health workers. This community service program aimed to improve the knowledge and skills of Posyandu cadres in providing nutrition education, measuring Mid-Upper Arm Circumference (MUAC), and conducting early detection of pregnant women at risk of CED. The program was implemented through training and mentoring activities involving 15 cadres from Posyandu Pandan Wangi RW 25, Cibeureum Village, South Cimahi District, Cimahi City. Evaluation was conducted using pre-tests and post-tests to assess knowledge, while skills were evaluated through direct observation using a checklist before and after the training. The results showed that the average knowledge score increased from 56.3 to 87.3. The average MUAC measurement skill score improved from 4.27 to 6.00 out of six assessed indicators, while nutrition education skill scores increased from 3.80 to 6.00. The achievement rate for MUAC measurement skills increased from 71.1% to 100%, whereas nutrition education skills increased from 63.3% to 100%. Training and mentoring activities for Posyandu cadres showed an increase in cadre capacity related to the prevention of KEK in pregnant women.